Risk factors for neurocysticercosis: A study from Northwest India - Mohit Girotra; Chanchal Gera; Rtika Ryfka Abraham; Paramdeep Kaur; Rajat Gauba; Yashpal Singh; Jeyaraj Durai Pandian (Wolters Kluwer Medknow Publications, 2014)
Background: Neurocysticercosis (NCC) is a common cause of epilepsy in the low- and middle-income countries. The risk factors for NCC vary from region to region. Aims: To study the risk factors NCC among patients with NCC and compare with age-and gender-matched controls without NCC. Setting and Design: Hospital-based case-control study. Materials and Methods: A total of 214 subjects were studied (109 NCC patients and 105 age- and gender-matched controls without NCC). The participants were selected from neurology and medical wards of a tertiary referral hospital in Northwest India. They were interviewed by trained medical interns using a questionnaire. Results: Patients with NCC were more likely to dispose garbage close to water source (P = 0.01), eat nonvegetarian food (P < 0.001), and often eat in restaurants (P < 0.001). Pigs were seen more in and around the NCC patient's houses than the control subjects residential areas (P = 0.001). A total of 15% of the NCC subjects lived close to slaughter houses, while only 2.7% of the control group stayed near a slaughter house (P = 0.002). Conclusions: Unhygienic practices, nonvegetarian food, and eating in restaurants were the risk factors for NCC in this study. There is an opportunity for prevention of NCC using public education.